The Influence of Pastor’s Leadership Style on The Faith Growth of The Congregation at GBT Kristus Ajaib Surabaya - Edom Purwoto, Rehuel Obed; Stella, Yunita; Wibowo, Daniel Ari (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Every member of the church is expected to experience ideal faith growth. However, in reality, many congregations still struggle to achieve this ideal growth. Even at GBT Kristus Ajaib Surabaya, several congregations face challenges in attaining ideal faith growth. These challenges include a tendency to become complacent with online worship, leading to laziness in attending physical services, and a misguided motivation for worship, driven by expectations of economic assistance in the form of money or groceries. The objective of this study is to investigate whether the pastor's leadership style influences the faith growth of the congregation at GBT Kristus Ajaib Surabaya. This research employs quantitative methods, with 78 church members participating as respondents. Data collection was conducted through a questionnaire and analyzed using simple linear regression. The leadership style instrument utilized in this study is based on the dimensional theory proposed by Paul Hersey and Ken Blanchard, while the faith growth instrument is based on the dimensional theory by Benson, Donahue, and Erickson. The analysis reveals a positive correlation between the pastor's leadership style and the congregation's faith growth. The study concludes that the pastor's leadership style significantly impacts the congregation's faith growth at GBT Kristus Ajaib Surabaya, accounting for 60.1% of the variance. Therefore, collaborative efforts are necessary from government bodies, synods, and local churches to foster further growth in the congregation's faith.